DECISION SUPPORT SYSTEM TO DETERMINE QUALITY TRADITIONAL SPICE FOR MAKING TURMERIC ACID USING WEIGHT PRODUCT METHOD - Miswan Gumanti; Oktafiani Oktafiani; Muhamad Muslihudin (STMIK Pringsewu Lampung, 2017)
Determining quality spices is one example of decision-making issues based on many factors or semi-structured criteria. Decision support system is part of one of the computer-based information systems commonly used to support decision making on a company's activities to find a very good traditional spice. Decision support system of the selection of traditional spices qualified in making herbal turmeric acid can be produced by using several methods, one of them is the weighted product (WP) method. Weighted product is one method of solving the problem that uses multiplication to connect the attribute value, where the value of each attribute must be raised first with the weight of attribute concerned. By using this product weihgted method, it is expected to help the research team to determine the selection of spices of very high quality. By using the decision support system and computerization, the quality of spice data can be stored therein, if there is an error in inputting the value or spice data herbal turmeric acid, then the wrong data can be repaired without re-input value or quality spice data.